JOSEPH SCACHT, TEORI SKEPTISISME HADIST DAN BANTAHAN SARJANA MUSLIM TERHADAPNYA (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2022)
This paper examines Joseph Schacht's skepticism about the originality of the hadith and the objections of Muslim scholars to the theory developed by the orientalists. The writing method uses a literature review based on related references. Schacht's work, "The Origins of Muhammadan Jurisprudence" contains ideas about hadith through three theories, namely Projecting Back Theory, Argumentum E Silentio Theory, and Common Link Theory. These three theories were refuted by Muslim scholars, saying that Schacht could not distinguish between the sirah of the prophet and the hadith. Schacht claims that the formation of classical fiqh is the result of the growth of hadith scholars, who have manipulated hadith to go against fiqh rules. The refutation of Muslim scholars is also aimed at the Projecting Back and Common Link theories as a theory of reconstructing the emergence of hadith sanad, which are considered not based on valid history.